Consumption in the Сrisis Сontext: Literature Review - Анна Тихомирова (Экономическая социология, 2025)
Consumption is a focal element of modern society. Dynamic by nature, it reflects diverse societal changes facilitated by a variety of external factors, including crises. Consumption practices in times of crisis have drawn considerable scholarly attention and are reflected in the vast amount of research that requires systematization and generalization. Given the significance of this topic, the research primarily aims to identify the main types of crises that draw scholarly attention in relation to consumption and to provide an overview of the scholarly literature focused on consumption practices during these crises. To achieve this goal, the mixed literature review approach, consisting of bibliometric analysis and systematic literature review, is adopted within the framework of the present study. In total, 48 multidisciplinary empirical research articles published between 2007 and 2024 and compiled using the set selection criteria, underwent analysis. In the selected corpus of research, three predominant types of crises are identified: economic/financial, energy, and COVID-19. This analysis extends beyond insights into consumer behavior, delving into crisis stressors, consumer coping practices, approaches to their analysis, and further research perspectives. The findings demonstrate a number of similarities and highlight significant differences in crisis discourses. The study contributes to the range of literature devoted to the analysis of consumption behavior in the crisis domain. It summarizes existing approaches and draws attention to existing research gaps and further research perspectives.